Technological barriers and strategies for overcoming them in the development of a charging station network - Anton Nedelko (The American Journal of Engineering and Technology, 2025)
The article examines challenges encountered in the process of establishing charging station networks for electric vehicles, proposes solutions to address them, and focuses on identifying barriers such as standard incompatibility, difficulties in implementing and using different types of devices, and power limitations. The methodological approach is based on the analysis and comparison of charging infrastructure models implemented in various countries, addressing current issues and development prospects. Based on the identified barriers, proposed solutions include equipment standardization, the creation of intelligent station management systems, and the modernization of power grids to meet growing demands. The findings indicate that the development of a charging station network requires consideration of multiple factors: technical standards, economic feasibility, and environmental safety requirements. The conclusions drawn will be useful for infrastructure developers, researchers in the field of sustainable transportation, and government entities involved in environmental and transportation policy. The conclusion emphasizes that overcoming technological barriers in creating an accessible and efficient charging station network is essential for the widespread adoption of electric vehicles, which will contribute to the development of a sustainable and environmentally friendly transportation system.